Hedgehog Antagonist REN(KCTD11) Regulates Proliferation and Apoptosis of Developing Granule Cell Progenitors - Argenti, Beatrice (J Neurosci, 2005)
During the early development of the cerebellum, a burst of granule cell progenitor (GCP) proliferation occurs in the outer external granule layer (EGL), which is sustained mainly by Purkinje cell-derived Sonic Hedgehog (Shh). Shh response is interrupted once GCPs move into the inner EGL, where granule progenitors withdraw proliferation and start differentiating and migrating toward the internal granule layer (IGL). Failure to interrupt Shh signals results in uncoordinated proliferation and differentiation of GCPs and eventually leads to malignancy (i.e., medulloblastoma). The Shh inhibitory mechanisms that are responsible for GCP growth arrest and differentiation remain unclear. Here we report that REN, a putative tumor suppressor frequently deleted in human medulloblastoma, is expressed to a higher extent in nonproliferating inner EGL and IGL granule cells than in highly proliferating outer EGL cells. Accordingly, upregulated REN expression occurs along GCP differentiation in vitro, and, in turn, REN overexpression promotes growth arrest and increases the proportion of p27/Kip1(+) GCPs. REN also impairs both Gli2-dependent gene transcription and Shh-enhanced expression of the target Gli1 mRNA, thus antagonizing the Shh-induced effects on the proliferation and differentiation of cultured GCPs. Conversely, REN functional knock-down impairs Hedgehog antagonism and differentiation and sustains the proliferation of GCPs. Finally, REN enhances caspase-3 activation and terminal deoxynucleotidyl transferase-mediated biotinylated UTP nick end labeling apoptotic GCP numbers; therefore, the pattern of REN expression, its activity, and its antagonism on the Hedgehog pathway suggest that this gene may represent a restraint of Shh signaling at the outer to inner EGL GCP transitions. Medulloblastoma-associated REN loss of function might withdraw such a limiting signal for immature cell expansion, thus favoring tumorigenesis.